2022
DOI: 10.3390/cancers14051305
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Ablation for Colorectal Liver Metastases: A Systematic Review and Pooled Oncological Analyses

Abstract: (1) Background: colorectal liver metastases (CRLM) are the most common extra-lymphatic metastases in colorectal cancer; however, few patients are fit for curative surgery. Microwave ablation (MWA) showed promising outcomes in this cohort of patients. This systematic review and pooled analysis aimed to analyze the oncological results of MWA for CRLM. (2) Methods: Following PRISMA guidelines, PubMed, Scopus, EMBASE, Google Scholar, Science Direct, and the Wiley Online Library databases were searched for reports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 49 publications
(86 reference statements)
1
14
0
Order By: Relevance
“…Confirming this, a recent systematic review ( 13 ), concluded that MW ablation for lesions smaller than 3 cm represents a safe and valid option of treatment with curative intent for selected patients with CRCLM, therefore overcoming the widespread concept among surgeons of a less oncological radicality with this alternative approach, at least in selected patients.…”
Section: Discussionmentioning
confidence: 80%
“…Confirming this, a recent systematic review ( 13 ), concluded that MW ablation for lesions smaller than 3 cm represents a safe and valid option of treatment with curative intent for selected patients with CRCLM, therefore overcoming the widespread concept among surgeons of a less oncological radicality with this alternative approach, at least in selected patients.…”
Section: Discussionmentioning
confidence: 80%
“…The results of relapse-free survival after 1, 3, and 5 years were 65.1, 44.6, and 34.4%, respectively, which is better than previously published data. 35 In the study of McEachron et al, it is noted that the lowest frequency of local relapses after MWA (4.4%) is achieved only if the ablation margin is 1 cm from the edge of the tumor. In the study, foci of 1.5 to 2.5 cm in size were ablated with two electrodes (the maximum ablation zone was 4.5 cm), and foci of 2.5 to 3.0 cm were ablated with three electrodes (the maximum ablation zone was 5.1 cm).…”
Section: Microwave Ablationmentioning
confidence: 97%
“…Cell death caused by microwave ablation is nearly identical to that produced by RFA. Microwave energy shows some advantages over RFA: the microwave ablation induces molecular oscillation and thermal energy delivery in tissues more distant from the probe site, obtaining wider, hotter ablation zones more quickly than RFA [ 29 ].…”
Section: Vascular and Non-vascular Approachesmentioning
confidence: 99%